1998
DOI: 10.1192/bjp.172.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine, appetitive and behavioural responses to d-fenfluramine in women recovered from anorexia nervosa

Abstract: Our results do not suggest that increased central 5-HT function is a trait marker in anorexia nervosa, but dysregulation in part of the central 5-HT system may be a vulnerability factor. The flattened post-meal response to cortisol in the subjects who had recovered from anorexia nervosa suggests that their hypothalamic pituitary--adrenal axis may be altered and deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 27 publications
0
47
0
1
Order By: Relevance
“…[13][14][15] In fact, most studies have shown that individuals with AN have disturbances of central serotonin activity, [15][16][17] which persist after recovery. [18][19][20] The opioid system has been implicated in the modulation of feeding behavior in which opioid agonists and antagonists were injected into animals. [21][22][23][24] Some clinical studies have suggested that opioid antagonists may have beneficial effects on eating behavior symptoms in patients with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In fact, most studies have shown that individuals with AN have disturbances of central serotonin activity, [15][16][17] which persist after recovery. [18][19][20] The opioid system has been implicated in the modulation of feeding behavior in which opioid agonists and antagonists were injected into animals. [21][22][23][24] Some clinical studies have suggested that opioid antagonists may have beneficial effects on eating behavior symptoms in patients with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, REC AN and BN subjects have higher than normal concentrations of CSF 5-HIAA, that is about 50% greater than CSF 5-HIAA levels found in the ill state ( Figure 1). In addition, REC AN and BN show altered behavioral responses to 5-HT challenges (65)(66)(67)(68) or other measures, such as platelet binding of paroxetine (69). As noted above, determining cause and effect is a major methodological confound in this illness.…”
Section: Serotoninmentioning
confidence: 99%
“…First, studies of women who have recovered from an eating disorder avoid the confounding effects of malnutrition on 5-HT activity. Second, some, but not all studies, showed that a disturbance of 5-HT activity persists after recovery from an eating disorder (Kaye et al, 1991;O'Dwyer et al, 1996;Ward et al, 1998). Finally, certain behaviors, such as anxiety, perfectionism, and obsessionality, have been found to occur premorbidly, and persist after recovery from AN (Bulik et al, 1997;Casper, 1990;Deep et al, 1995;Srinivasagam et al, 1995;Strober, 1980).…”
Section: Introductionmentioning
confidence: 99%